Improving the role of equity crowdfunding in Europe's capital markets - Karen E. Wilson; Marco Testoni (Bruegel, 2014)
Crowdfunding is a growing phenomenon that encompasses several different models of financing for business or other ventures. Despite the hype, equity crowdfunding is still the smallest part of the crowdfunding market. Because of its legal framework, Europe has been at the forefront of equity crowdfunding market development. Equity crowdfunding is more complex than other forms of crowdfunding and requires proper checks and balances if it is to provide a viable channel for financial intermediation in the seed and early-stage market in Europe. It is important to explore this new channel of funding for young and innovative firms given the critical role these start-ups can play job creation and economic growth in Europe. We assess the potential role of equity crowdfunding in the overall seed and early-stage financing market and highlight the potential risks of equity crowdfunding. We describe the current state of play in this nascent industry, considering both the innovations introduced by market operators and existing regulation. Currently in Europe there is a patchwork of national legal frameworks related to equity crowdfunding and this should be addressed in a harmonised way.
Keywords: 330